Interventions to improve vitamin D status in at-risk ethnic groups during pregnancy and early childhood: a systematic review. Issue 11 (17th August 2021) - Tanna, Nuttan K; Alexander, Emma C; Lee, Charlotte; Lakhanpaul, Monica; Popat, Rickin M; Almeida-Meza, Pamela; Tuck, Alice; Manikam, Logan; Blair, Mitch
Abstract: Objective: To systematically review the literature with the primary aim of identifying behavioural interventions to improve vitamin D stores in children from at-risk ethnic groups. Design: Review based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. PROSPERO registration number: CRD42017080932. Health Behaviour Model and Behaviour Change Wheel framework constructs used to underpin evaluation of interventions. Methodological quality evaluated using Cochrane Risk of Bias, Cochrane ROBINS-I and NHLBI tools. Setting: Databases Cochrane Library, MEDLINE, EMBASE, CINAHL with secondary search of Google Scholar. No country limits set. Papers between January 1990 and February 2018, published in English included. Anticipating study heterogeneity, outcome measures not pre-specified and identified from individual full papers. Updated literature search November 2020. Participants: Patient or population including pregnant women, newborns and children aged under 18 years, from Asian or African ethnic groups. Results: Of 10 690 articles screened, 298 underwent full-text review, with 24 ultimately included for data extraction. All identified studies conducted a vitamin D pharmacological supplementation intervention, with two also incorporating a behavioural intervention strategy. No study explicitly defined a primary aim of evaluating a behavioural intervention, undertaken to study its effect on vitamin D supplement uptake. Conclusions: There is a need to address the paucity of data in ethnic at-risk children on how behavioural interventions ideally developed and co-produced with the community under study, affect and help improve vitamin D uptake, within the antenatal and pregnancy phase as well as during childhood.